(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2021)
The article examines the tasks of the National Police of Ukraine as a subject of implementation of the preventive function of the state. It is emphasized that the tasks of the Department of Preventive Activities of the National Police of Ukraine are an important component of determining the specifics of its activities and administrative and legal status, as the effective implementation of the Department of Preventive Activities of the National Police of Ukraine depends on a clear legislative understanding of its tasks as body of state power. It is noted that the implementation of the tasks of the National Police in Ukraine means that policing is based on the principles enshrined in current legislation, taking into account current trends in European integration. The principles as guiding ideas that underlie the functioning of each police body and unit are designed to promote the further development of the police as a European-style institution. In turn, the tasks of the police determine the means of policing, based on the relevant principles. It is emphasized that the main tasks of the Department of Preventive Activities of the National Police of Ukraine are to organize and ensure within the competence of the National Police of Ukraine the functions of Ukrainian legislation to maintain public safety and order, protect human rights and freedoms, and individual preventive work aimed at preventing the commission of administrative and criminal offenses, preventing and combating domestic violence, escorting persons detained on suspicion of committing a criminal offense, taken into custody, accused, sentenced to arrest or imprisonment, and for a term of imprisonment in the courtroom. It was emphasized that the general tasks of the Department of Preventive Activities of the National Police of Ukraine include: ensuring public safety and public order; protection of fundamental human rights and freedoms, as well as the interests of society and the state; providing, within the limits established by law, services to assist persons who, for personal, economic, social reasons or due to emergencies, need such assistance. It is noted that the special tasks of the Department of Preventive Activities of the National Police of Ukraine include: implementation of state policy in the field of combating violence; preventive measures; introduction of programme preventive means for systematization of violent incidents, general and individual preventive work aimed at preventing the commission of administrative and criminal offenses, prevention and counteraction to domestic violence.